2012
DOI: 10.1177/0961463x12450242
|View full text |Cite
|
Sign up to set email alerts
|

Gendered working-time arrangements and their policy implications: Korean experiences

Abstract: This study is to explore the reality of gendered work time and its policy implications. With the dual-earner model of family, the amount and manner in which time is spent for paid work, as opposed to unpaid work, constructs gender relations in Korea. This article raises the following questions. What is the impact of exceptionally long working hours on gender relations in the workplace and the family in Korea? In terms of time spent, to what extent are there changes in the unquestioned exclusive care responsibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…In a line very similar to the studies of Myrie and Daly (2009) and Won (2012), the three aforementioned models show that time does not remain immune from a significant process of resignification of the family space and, more specifically, of the home. Once the women have completed this process, they state that working at home or on site at their company becomes irrelevant.…”
Section: Subverting Long-working Hourssupporting
confidence: 65%
See 1 more Smart Citation
“…In a line very similar to the studies of Myrie and Daly (2009) and Won (2012), the three aforementioned models show that time does not remain immune from a significant process of resignification of the family space and, more specifically, of the home. Once the women have completed this process, they state that working at home or on site at their company becomes irrelevant.…”
Section: Subverting Long-working Hourssupporting
confidence: 65%
“…These studies suggest that there is a shift towards a more complex view of temporality in order to recognise the complexity and deep interconnectedness of various types of “work” and “life” (Moreno-Colom, 2017). In addition to utilising time, teleworkers use designated home workspaces strategically to segment the work–home boundary and avoid home-based interruptions (Myrie and Daly, 2009; Won, 2012). In this sense, the physical boundaries are manipulated in order to engage with certain tasks and particular equipment is used to create special environments (Carrasco and Domínguez, 2015; Gold and Mustafa, 2013).…”
Section: Telework: a Spatial And Temporal Restructuringmentioning
confidence: 99%
“…Irrespective of the Korean (Song, Jang, & Kim, ; Won, ) or western context (Stone & Hernandez, ; Williams et al, ), time commitment is ‘prima facie evidence of commitment' (Stone & Hernandez, , p. 236). Yet, the experiences of Korean fathers clearly confirm the power of the time commitment and the nature of the Korean working‐time regime as excessively long working hours (OECD, ).…”
Section: Resultsmentioning
confidence: 99%
“…The Korean time regime characterized by excessively long working hours is another piece of prime evidence that confirms the power of the work devotion schema (Won, 2012). According to OECD (2016b), annual working time in Korea is 2071 hours, the second longest in the world, following Mexico of 2348 hours.…”
Section: The Work Devotion Schema and The Poor Worker Stigmamentioning
confidence: 95%
“…As other studies have shown, even in times of economic prosperity, cultural change in work practices takes time and needs to be led by line managers and CEOs (Haas et al, 2000;North, 2012). In addition the presence and legacy of deep-seated patriarchal gender norms (son preference; strict father, kind mother values) in many Asian countries continue to shape perceptions of entitlement and preference in the workplace (Won, 2012).…”
Section: Working Time Innovation and Support Measuresmentioning
confidence: 99%